Cover Image. Issue 4 (12th March 2018) - Yoris, Adrián; Abrevaya, Sofía; Esteves, Sol; Salamone, Paula; Lori, Nicolás; Martorell, Miguel; Legaz, Agustina; Alifano, Florencia; Petroni, Agustín; Sánchez, Ramiro; Sedeño, Lucas; García, Adolfo M.; et al.
Abstract : COVER ILLUSTRATION: In this cover artwork, our aim is to show the brain‐heart communication and its possible deficits, located on the anatomical and functional structure of the cardiovascular system, which is altered in hypertension. We also highlight the three key interoceptive areas at the CNS level: the insula, anterior cingulate (ACC) and somatosensory cortices. Finally, the cover highlights the core nodes (blue, aortic arch; green, vagal system; and orange, insula, ACC and somatosensory cortex) that could be implied in the brain‐heart communication and interoception.